2021
DOI: 10.1371/journal.pone.0236685
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of direct carbon emissions of Chinese provinces using artificial neural networks

Abstract: Closely connected to human carbon emissions, global climate change is affecting regional economic and social development, natural ecological environment, food security, water supply, and many other social aspects. In a word, climate change has become a vital issue of general concern in the current society. In this study, the carbon emission data of Chinese provinces in 1999–2019 are collected and analyzed, so as to identify the carbon emission of direct consumption per 10,000 residents in each province (includ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Huang et al (2019) employed long short-term memory (LSTM) networks to forecast annual total carbon emissions (Huang et al, 2019). Jin et al (2021) used Elman neural networks (ENNs) to predict carbon emissions from direct consumption by residents for the upcoming year (Jin, 2021). Jena et al (2021) applied multilayer artificial neural network modeling (MLANN) to predict the annual total carbon emissions of various countries (Jena et al, 2021).…”
Section: Artificial Intelligence Modelsmentioning
confidence: 99%
“…Huang et al (2019) employed long short-term memory (LSTM) networks to forecast annual total carbon emissions (Huang et al, 2019). Jin et al (2021) used Elman neural networks (ENNs) to predict carbon emissions from direct consumption by residents for the upcoming year (Jin, 2021). Jena et al (2021) applied multilayer artificial neural network modeling (MLANN) to predict the annual total carbon emissions of various countries (Jena et al, 2021).…”
Section: Artificial Intelligence Modelsmentioning
confidence: 99%
“…For the prediction of total CEs, most of the existing studies used the partial least squares regression method, the STIRPAT model, and the scenario analysis method to predict the peak of China's CE, and some scholars combined various methods to predict China's CEs (Yang et al, 2018;Li et al, 2021). Jin et al used the radial basis function (RBF) to predict the urban CE content in China from 2027 to 2032 (Jin, 2021). The experimental results showed that the number of samples will affect the prediction ability and network structure complexity of RBF, and the network is not suitable for large sample data prediction.…”
Section: Prediction Of Cementioning
confidence: 99%
“…To offer a scientific foundation for CE management and planning, the trend and characteristics of changes in CE between 2027 and 2032 are studied and anticipated based on data on direct CEs of people of Chinese provinces from 1999 to 2019. The weighted factors included as input data were residential energy consumption types, CO2 emission coefficients, electrical CE coefficients, and populations (total, urban, and rural) [7].…”
Section: Local Ce Predictionmentioning
confidence: 99%
“…To offer a scientific foundation for CE management and planning, the trend and characteristics of changes in CE between 2027 and 2032 are studied and anticipated based on data on direct CEs of people of Chinese provinces from 1999 to 2019. The weighted factors included as input data were residential energy consumption types, CO2 emission coefficients, electrical CE coefficients, and populations (total, urban, and rural)[7].Within this paper, three types of artificial neural networks were discussed (Backpropagation Neural Network (BPNN), Radial Basis Function (RBF), and Elman neural network). After considering prediction accuracy, the complexity of construction, robustness, and fault tolerance, the Elman neural network seems to be the best one (Figure5).…”
mentioning
confidence: 99%